SCHOOL AND PARENT PERCEPTIONS OF GRADUATION POLICY AT HIGH SCHOOL LEVEL AT SMA SWASTA YPI DHARMA BUDI - Rahman, Anisah; Dora, Nuriza (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This research aims to explore the perceptions of the school and parents regarding the graduation policy which is currently being widely discussed. Graduation at the high school level is often an important moment that marks the end of the study period at the high school level, but policies related to its implementation are still being debated, both from an educational and social perspective. The reason for choosing this topic is because there are many different views regarding the urgency and ideal form of graduation. Researchers used qualitative research with a case study method. The research results show that the school views the graduation policy as an important tradition that appreciates students' efforts and achievements, as well as marking the end of their academic journey and preparation for higher education or the world of work. Parents generally have a positive view, viewing graduation as a reward for their children's hard work. -their children and a historic moment worth celebrating. However, there are also those who think that graduation at the high school level should be simpler. The main obstacles for parents include limited time due to busy work and financial costs. This research concludes that graduation policies need to be designed by considering a balance between symbolic and practical needs and involving active participation from all stakeholders. These results are important for providing a more comprehensive understanding of the implications of graduation policies for school communities and can be a reference in making more inclusive and effective policies in the future.